Effects of lavender essential oil inhalation aromatherapy on postoperative sleep quality in patients with intracranial tumors: a randomized controlled trial - Yang Liu; Yanmei Dong; Yanmei Dong; Xin Wang; Yeqin Huang; Yeqin Huang; Fan Wu; Fei Xia; Fei Xia; Hongtong Bai; Hongtong Bai; Hui Li; et al. (Frontiers in Pharmacology)
PurposeTo investigate the effects of lavender essential oil (LEO) on postoperative sleep quality and perioperative neurocognitive disorders (PNDs) in patients with intracranial tumors.Patients and methodsThis study was a randomized controlled trial in which all patients were randomly assigned to either the control group, which received no intervention, or the experimental group, which received LEO. Postoperative sleep quality was assessed using a dedicated sleep monitor. The PNDs were evaluated by the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) and the Mini-Mental State Examination (MMSE), using education-adjusted cutoffs recommended by the latest Chinese Dementia Guidelines (2023).ResultsCompared with the control group, the total sleep duration and the deep sleep duration were significantly longer in the experimental group only on the fourth postoperative day (418.48 ± 21.95 vs. 389.57 ± 49.29, P = 0.019; 95.10 ± 19.98 vs. 66.86 ± 32.69, P = 0.002). The experimental group exhibited significantly shorter sleep latency compared with the control group (13.24 ± 8.46 vs. 28.62 ± 19.86; p = 0.002). Additionally, the apnea-hypopnea index and frequency of awakenings were lower in the experimental group (14.05 ± 9.85 vs. 21.00 ± 10.78; p = 0.035; 2.67 ± 1.32 vs. 5.05 ± 2.97; p = 0.002). The duration of postoperative delirium was shorter in the experimental group compared with the control group (2.00 ± 0.82 vs. 3.80 ± 1.30; p = 0.048). On the seventh postoperative day, participants in the experimental group had lower anxiety scores than those in the control group (3.38 ± 2.27 vs. 6.14 ± 5.43; p = 0.038).ConclusionLEO inhalation aromatherapy could effectively improve postoperative sleep quality, particularly on the fourth postoperative day. It also positively impacted anxiety and reduced the duration of postoperative delirium.Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2300073091.